Propuesta de intervención urbano-paisajístico para la conservación de humedales ribereños del río Tena en la ciudad de Tena - Aguinda Ashanga, Heydi Liseth (2026)
The city of Tena maintains a close relationship with its hydrological systems, which provide essential environmental functions such as flood regulation, water purification, and biodiversity conservation. However, unplanned urban growth, the informal occupation of water protection buffer zones, and weak enforcement of regulations have led to the progressive degradation of the riparian wetlands of the Tena River. The research identifies issues such as untreated wastewater discharges, loss of native vegetation cover, ecological fragmentation, and a disconnection between the riparian edge and the urban fabric, which increases vulnerability to flooding. Using a mixed methodological approach, the study reveals a lack of coordination between urban planning and ecosystem functions. In response, an urban–landscape intervention based on nature-based solutions is proposed, structured as a riparian corridor that integrates green–blue infrastructure, ecological restoration, and public spaces adapted to fluvial dynamics, contributing to territorial resilience and improving the quality of life in the city of Tena.